Modifikasi Bioplastik Berbasis Pati-Polivinil Alkohol (PVA) Dengan Cross-Linking Agent Asam Sitrat Dan Pemplastis Sorbitol - Yoga Pratama; Bahruddin Bahruddin; Idral Idral (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Bioplastic characteristics are influenced by various parameters, including levels of cross linking agents (such as citric acid) and plasticizers (such as sorbitol). The research was to study the effect of citric acid and sorbitol levels on mechanical properties, cross linking (characterized by ester groups), and biodegradation of bioplastics based starch-polyvinyl alcohol (PVA). Bioplastic manufacturing is done by mixing sago starch -PVA (1: 3), sorbitol (10, 15, 20% w/w) and citric acid (2.5; 5; 7.5% w/w) at 90ºC for 55°C minutes, optimization of process conditions is determined by response surface methodology (RSM). The parameters tested include tensile strength test, elongation, and biodegradation. The most significant factor affecting all responses was the level of citric acid and sorbitol. The optimum process conditions were obtained at 4.8% w / citric acid content and sorbitol 11.4% w / w with a tensile strength response of 26,34 MPa, elongation 379%, and 49,18% biodegradation. Keywords: bioplastics, citrid acid, sorbitol, polyvinyl alcohol, RSM, sago starch